Effects of post-deposition treatment on zinc sulfide thin films prepared by an effective-cost chemical bath deposition method - Arsad A.Z.; Arzaee N.A.; Abdullah S.F.; Rahman M.N.A.; Noh M.F.M.; Bahruddin M.S.; Za'abar F.I.; Doroody C.; Harif M.N.; Ibrahim N.B.; Zuhdi A.W.M. (Elsevier Ltd, 2025)
Zinc sulfide thin films have been prepared through the effective-cost chemical bath deposition (CBD), utilizing various post-deposition treatments (PDT). PDT parameters like ammonia concentration, dipping time, and ultrasonic cleaning (UC) were investigated. The study found that ZnS thin film surface morphologies differ before and after PDT. The untreated film has an impurity phase with distinct morphology, low transmittance, carrier concentrations, and mobility values. PDT films tailored to non-crystalline phases resulted in lower thickness, improved transmittance, and enhanced carrier concentrations and mobility values compared to untreated film. XPS findings demonstrate that various PDT changes in the film composition eliminate sulfate and Zn(OH)2 and increase ZnO bonds. Simultaneous NH4OH and UC lead Zn?O bond peaks to dominate and band gap deterioration compared to untreated ZnS thin film. The ZnS thin films treated with 20% NH4OH without UC exhibited excellent properties, including structure prominent of Zn?S and Zn?O bond peaks, 106 nm thickness growth, 95% average transmittance, 3.70 eV band gap, 3.67 ? 1011 cm?3 carrier concentration, 3.95 ? 102 cm2V?1S?1 mobility, and 4.30 ? 104 cm resistivity. These values can be ideal for implementing buffer layers on copper indium gallium selenide (CIGS) solar cells. The PDT approach can improve the properties of ZnS thin films, which is crucial to reducing costs in solar cell production. ? 2024